2016
DOI: 10.1007/s40037-016-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative clinical and population-based curriculum for medical students to address primary care needs of the homeless in New York City shelters: Teaching homeless healthcare to medical students

Abstract: Background Millions of Americans experience homelessness annually. Medical providers do not receive adequate training in primary care of the homeless.Methods Starting in 2012, a comprehensive curriculum was offered to medical students during their family medicine or ambulatory clerkship, covering clinical, social and advocacy, population-based, and policy aspects. Students were taught to: elicit specific social history, explore health expectations, and assess barriers to healthcare; evaluate clinical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Additionally, in-service curriculum focused specifically on health care for homeless persons might improve providers’ skills in communicating and developing rapport with homeless persons with MHSUDs. For example, one study found curriculum focused on health care for homeless persons increased providers’ understanding of challenges facing homeless persons, and improved providers’ communication skills and self-efficacy in managing care for homeless patients (Asgary, Naderi, Gaughran, & Sckell, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in-service curriculum focused specifically on health care for homeless persons might improve providers’ skills in communicating and developing rapport with homeless persons with MHSUDs. For example, one study found curriculum focused on health care for homeless persons increased providers’ understanding of challenges facing homeless persons, and improved providers’ communication skills and self-efficacy in managing care for homeless patients (Asgary, Naderi, Gaughran, & Sckell, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…All articles except for Powell and Bullock explicitly described programs that used traditional didactic forms of instruction [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]79 (20) and many described participatory components that were also classroom-based: case-based instruction 59,60,63,69,70,73,77 (7); small group work 61,63,69,77,80 (5); and peer teaching 59,66,67,71,78 (5). All learner-led activities were considered participatory within our charting scheme.…”
Section: Educational Methodsmentioning
confidence: 99%
“…Experiential learning was defined as activities involving direct interactions with patients, families, and communities. Clinic-based learning was integrated into clerkships or electives 59,66,67,71,78 (5). Community-based education took the form of service projects 61, 62, 65, 66, 68, 70, 71, 73-75, 78, 80 (12); community-based participatory research 62,74 (2); and neighborhood tours 69,72,75 (3).…”
Section: Educational Methodsmentioning
confidence: 99%
See 2 more Smart Citations